4. Internet Audio Products - Weaver, Duane; Guspie, Deborah; Cox, Nolan; Baggaley, Jon (International Review of Research in Open and Distributed Learning, 2002)
Online audio methods have evolved as a means of providing unlimited and inexpensive/free international audio communication. They are becoming popular in distance education (DE) as an alternative to the asynchronous conferencing methods (Report 3 in this series). Current types of Internet audio connectivity provide: (a) direct between individuals (Internet phone); (b) shared places or forums on the Internet where groups can meet (audio-conferencing); and (c) a variety of PC-to-PC and PC-to-phone methods. However, products differ in terms of lag time, delay, quality of voice, and stability of service and connection. The report compares current online audio packages in terms of their technical features and reliability.